Three-Dimensional Compared with Two-Dimensional Preoperative Planning of Corrective Osteotomy for Extra-Articular Distal Radial Malunion: A Multicenter Randomized Controlled Trial. (18th July 2018) - Buijze, Geert A.; Leong, Natalie L.; Stockmans, Filip; Axelsson, Peter; Moreno, Rodrigo; Ibsen Sörensen, Allan; Jupiter, Jesse B.
Abstract : Background: Malunion is the most frequent complication seen after a fracture of the distal end of the radius. The primary aim of this study was to compare patient-reported outcome measures (PROMs) after corrective osteotomy for malunited distal radial fractures with and without 3-dimensional (3D) planning and use of patient-specific surgical guides. Methods: From September 2010 to May 2015, 40 adult patients with a symptomatic extra-articular malunited distal radial fracture were randomized to 3D computer-assisted planning or conventional 2-dimensional (2D) planning for corrective osteotomy. The primary outcome was the Disabilities of the Arm, Shoulder and Hand (DASH) score. Secondary outcomes included the Patient-Rated Wrist Evaluation (PRWE) score, pain and satisfaction scores, grip strength, and radiographic measurements at 3, 6, and 12 months postoperatively. Results: From baseline to 12 months of follow-up, the reduction in the mean DASH score was −30.7 ± 18.7 points for the 3D planning group compared with −20.1 ± 17.8 points for 2D planning (p = 0.103). Secondary functional outcome by means of the PRWE resulted in a similar reduction of −34.4 ± 22.9 points for the 3D planning group compared with −26.6 ± 18.3 points for the 2D planning group (p = 0.226). There were no significant differences in pain, satisfaction, range of motion, and grip strength. Radiographic analysis showed significant differences in the mean residual volar angulation (by 3.3°; p = 0.04) and radial inclination (by 2.7°; p = 0.028) compared with the templated side, in favor of 3D planning and guidance. The duration of preoperative planning and surgery as well as complication rates were comparable. Conclusions: Although there was a trend toward a minimal clinically important difference in PROMs in favor of 3D computer-assisted guidance for corrective osteotomy of extra-articular distal radial malunion, it did not attain significance because of (post hoc) insufficient power. Despite the challenge of feasibility, a trial of large magnitude is warranted to draw definitive conclusions regarding clinical advantages of this advanced, more expensive technology. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.